2022
DOI: 10.5093/clysa2022a8
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Moderates the Associations between Bipolar Disorder Mood Episodes and Mental Health

Abstract: Bipolar disorders (BD) are a group of debilitating chronic mood disorders characterized by repeated recurrence of (hypo)manic and depressive episodes alternating with euthymic periods during which mood disturbances are significantly subsided (American Psychiatric Association [APA, 2013]). Hypomanic and manic episodes are characterized by abnormal and persistent elevated mood. However, for a diagnosis of a manic episode, the duration of elevated mood must be prolonged in time, of greater severity, and usually r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…It has also been hypothesized that there may be an association between resilience and functioning [25], in which patients with higher resilience show better psychosocial functioning [21]. In our study, we have found a significant correlation between resilience and functioning, indicating that OABD with lower resilience also have poorer psychosocial functioning.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…It has also been hypothesized that there may be an association between resilience and functioning [25], in which patients with higher resilience show better psychosocial functioning [21]. In our study, we have found a significant correlation between resilience and functioning, indicating that OABD with lower resilience also have poorer psychosocial functioning.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, resilience is seen as a dynamic multidimensional construct that not only involves personal characteristics, abilities, or skills, but also family support and other external factors [24]. Because it also includes contextual resources, which may be learned and acquired, resilience is considered a process rather than a trait [25]. Some "resilience factors" or coping mechanisms include an optimistic but realistic outlook, sturdy role models, an inner moral compass, religious or spiritual practices, acceptance of what cannot be changed, physical fitness, mental sharpness, emotional strength, actively solving problems while looking for meaning and opportunity, and humor [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, levels of hope and resilience were higher in those patients reporting lower psychopathology and suicidal risk: unipolar patients have shown less severe clinical profile reporting higher levels of resilience and hope. This may reflect the evidence that resilience moderates the relationship between severity of depressive episodes in bipolar disorder and subjective well-being, including the feeling of hope/hopelessness (Echezarraga et al, 2022). Consistently, the hope and resilience scores have shown a positive correlation between each other, as converging factors in the framework of recovery and well-being (Duggal et al, 2016; Nash, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…In fact, resilience and recovery may show several factors in common in the context of mental health and psychological disorders, including the occurrence of adversity and the employment of internal personal strengths and environmental resources: this may suggest that interventions promoting resilience are positively impacting on mental health outcomes and rates of resilience (Echezarraga et al, 2019; Shrivastava & Desousa, 2016). Resilience is said to moderate the associations between bipolar disorders mood episodes and mental health and well-being with a final authors’ recommendation to employ interventions promoting disorder-specific resilience factors (Echezarraga et al, 2022). Jagfeld et al (2021) proposed a conceptual revision of recovery model based on CHIME (Connectedness, Hope and Optimism, Identity, Meaning, Empowerment; Leamy et al, 2011) in the context of Bipolar Disorder and launched the framework named POETIC including six factors as following: Purpose and Meaning, Optimism and Hope, Empowerment, Tensions, Identity, Connectedness.…”
Section: Introductionmentioning
confidence: 99%